Endometriosis as a risk factor for colorectal cancer - Vargas-Hernández, Víctor Manuel; Tovar- Rodríguez, José María; Vargas-Aguilar, Víctor Manuel (Clinical Journal of Obstetrics and Gynecology, 2020)
Endometriosis is a common benign disease in women of reproductive age, it has been associated with an increased risk of various malignancies that is defined by certain histological criteria mainly 80% in ovary and 20% in extragonadal sites such as intestine, rectovaginal septum, abdominal wall, pleura and others; the greatest risk for colorectal cancer is women with adenomyosis or endometriosis; Several genetic alterations have been found in the risk of endometriosis associated with cancer; The symptomatology, imaging and endoscopic characteristics simulate other inflammatory and malignant lesions that make the preoperative diagnosis of extragonadal endometriosis difficult. This is a review of the knowledge about endometriosis and its potential risk of malignancy, particularly with colorectal cancer